Group B streptococcal carriage among pregnant women and its implications - Kandi, Venkataramana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Group B streptococci are a group of gram positive cocci of Streptococcaceae family belonging to Lancefield group B, classified based on carbohydrate antigen. Streptococci are a group of gram positive cocci predominantly showing chain arrangement attributed to the type of cell division (linear). Among the various groups of streptococci group B Streptococci comprise normal micro biota of human genitourinary tract. Group B Streptococci are represented by Streptococcus agalactiae which are not only commensals but also recognized as a potential pathogen responsible for serious neonatal infections. Colonization in vagina prior to pregnancy may be considered as a risk factor for intra-partum and post-partum complications in pregnant women and neonates. Considering the fact that there are many serotypes of group B streptococci prevalent in different geographical regions and that there are no vaccine available, studies on epidemiology of colonization among risk groups and potential pathogenic nature of the colonizing bacteria assume significance. This paper enlivens the current knowledge of epidemiology of group B Streptococci.